Giant obstructive myxoma presenting as mitral valve obstruction with severe pulmonary hypertension. - Sawadogo, Adama; Tamboura, Yacouba; Doumbia, Modibo; Diarra, Ibrahima Baba (Nepalese Heart Journal, 2018)
Cardiac myxomas may have different clinical presentations that may expose the patient to sudden death due to obstruction of the left ventricle inflow. The authors report a case of 34 years old male who was diagnosed with left atrial myxoma that presented as mitral valve obstruction with severe pulmonary hypertension. He underwent emergent sternotomy under cardiopulmonary bypass and the myxoma was successfully removed. The postoperative course was uneventful.